Improving the Quality of Education Through Higher Education Management - Rasfiuddin Sabaruddin; Galih Firdaus; Hafid Bahar (Jurnal Kewarganegaraan, 2022)
AbstractTo improve the quality of education to the maximum, it is necessary to increase the performance and quality of the elements of education on an ongoing basis. Improving the quality of education can be done by implementing Total Quality Management (TQM) for higher education institutions. This research then aims to see how the education quality in Indonesia can be improved through higher education management. This research will be conducted utilizing a qualitative methodology. The data used in this study were derived from a variety of research outcomes and prior studies that were still relevant to this study. This study demonstrated that customer satisfaction is an indicator of the efficacy of quality management in higher education. Higher education can be effective if it meets the needs of "educational customers" and produces desirable goods, especially for the general public.Keywords: Quality of Education, Higher Education, Management.